Functional Mutation of Multiple Solvent-Exposed Loops in the Ecballium elaterium Trypsin Inhibitor-II Cystine Knot Miniprotein - Kimura, Richard H.; Jones, Douglas S.; Jiang, Lei; Miao, Zheng; Cheng, Zhen; Cochran, Jennifer R. (PloS one, 2011)
The Ecballium elaterium trypsin inhibitor (EETI-II), a 28-amino acid member of the knottin family of peptides, contains three interwoven disulfide bonds that form multiple solvent-exposed loops. Previously, the trypsin binding loop of EETI-II has been engineered to confer binding to several alternative molecular targets. Here, EETI-II was further explored as a molecular scaffold for polypeptide engineering by evaluating the ability to mutate two of its structurally adjacent loops. Yeast surface display was used to engineer an EETI-II mutant containing two separate integrin binding epitopes. The resulting knottin peptide was comprised of 38 amino acids, and contained 11- and 10-residue loops compared to wild-type EETI-II, which naturally contains 6- and 5-residue loops, respectively. This knottin peptide bound to α(v)β(3) and α(v)β(5) integrins with affinities in the low nanomolar range, but bound weakly to the related integrins α(5)β(1) and α(iib)β(3). In addition, the engineered knottin peptide inhibited tumor cell adhesion to vitronectin, an extracellular matrix protein that binds to α(v)β(3) and α(v)β(5) integrins. A (64)Cu radiolabeled version of this knottin peptide demonstrated moderate serum stability and excellent tumor-to-muscle and tumor-to-blood ratios by positron emission tomography imaging in human tumor xenograft models. Tumor uptake was ∼3-5% injected dose per gram (%ID/g) at one hour post injection, with rapid clearance of probe through the kidneys. We demonstrated that multiple loops of EETI-II can be mutated to bind with high affinity to tumor-associated integrin receptors. The resulting knottin peptide contained 21 (>50%) non-native amino acids within two mutated loops, indicating that extended loop lengths and sequence diversity were well tolerated within the EETI-II scaffold. A radiolabeled version of this knottin peptide showed promise for non-invasive imaging of integrin expression in living subjects. However, reduced serum and metabolic stability were observed compared to an engineered integrin-binding EETI-II knottin peptide containing only one mutated loop.